A 2-year integrated agriculture and nutrition and health behavior change communication program targeted to women in Burkina Faso reduces anemia, wasting, and diarrhea in children 3–12.9 months of age at baseline: A cluster-randomized controlled trial - Olney, Deanna K.; Pedehombga, A.; Ruel, Marie T.; Dillon, A. (Elsevier, 2015)
Background: Among young children in Burkina Faso, anemia and chronic and acute undernutrition are widespread. Objective: This study assesses the impact of Helen Keller International's (HKI) 2-y integrated agriculture [homestead food production (HFP)] and nutrition and health behavior change communication (BCC) program, targeted to women, on children's (3–12.9 mo old at baseline) anthropometry (stunting, wasting, and underweight), mean hemoglobin (Hb), anemia (Hb < 11 g/dL), and diarrhea prevalence. Methods: We used a cluster-randomized controlled trial, with 55 villages randomly assigned to a control group (n = 25) or 1 of 2 treatment groups (n = 15 each), which differed by who delivered the BCC messages [older women leaders or health committee (HC) members]. We used difference-in-difference (DID) estimates to assess impacts on child outcomes. Results: We found marginally significant (P < 0.10) impacts on Hb (DID: 0.51 g/dL; P = 0.07) and wasting [DID: −8.8 percentage point (pp); P = 0.08] and statistically significant (P < 0.05) impacts on diarrhea (−15.9 pp; P = 0.00) in HC compared with control villages among children aged 3–12.9 mo and larger impacts for anemia (DID: −14.6 pp; P = 0.03) and mean Hb (DID: 0.74 g/dL; P = 0.03) among younger children (aged 3–5.9 mo). However, we found no significant impacts on stunting or underweight prevalence. Plausibility was supported by greater improvements in women’s agricultural production and maternal infant and young child feeding and care knowledge and practices in HC compared with control villages. Conclusions: HKI’s 2-y integrated HFP+BCC program (HC group) significantly improved several child outcomes, including wasting (marginal), diarrhea, Hb, and anemia, especially among the youngest children. This is the first cluster-randomized controlled trial of an HFP program that documents statistically significant positive effects on these child nutrition outcomes. This trial was registered at clinicaltrials.gov as NCT01825226.